ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP EARNING MANAGEMENT PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Surenggono, Surenggono (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2012)
Earning management is the moral hazard problems of the manager. Earning management occurs because there is a conflict of interest between the managers as agents and shareholders (principal) as owners of the company. Earning management will affect reported earnings. This study aims to determine the effect of good corporate governance in the form of the proportion of independent directors, audit committees, institutional ownership, managerial ownership, and the quality of audit on earning management. Sampling technique using purposive sampling with the following criteria: banking companies listed on the Indonesian Stock Exchange (BEI) since 2007 and is still listed as the issuer until the year 2009, published financial statements as of December 31, no merger, no acquisition and no restructuring during the study period (2007 – 2009). Based on these criteria, there are 15 companies that can be sampled. The results of hypothesis testing using multiple regression shows that good corporate governance in the form of the proportion of independent directors, audit committees, institutional ownership, managerial ownership, and audit quality do not significantly affect earnings management.